The crucible [videorecording (DVD)] - Hytner, Nicholas; Miller, Arthur, 1915-2005; Day-Lewis, Daniel; Ryder, Winona, 1971-; Scofield, Paul, 1922-2008; Allen, Joan, 1956-; Miller, Arthur, 1915-2005 (Twentieth Century Fox Home Entertainment, 2011)
A group of teenage girls meets in the woods at midnight for a secret ceremony. When the ceremony is witnessed by the town minister, the girls are accused of witchcraft. Soon the entire village is consumed by hysteria, and innocent victims are put on trial, leading to a devastating climax.